Mountain Ice and Water : investigations of the hydrologic cycle in alpine environments - Shroder, John F.; Greenwood, Gregory B. (Saint Louis : Elsevier Science, 2016)
"Covers major water and ice issues pertaining to planetary dynamics, sustainable development, and new thinking on mountain ice and water that help plan for an uncertain future in the face of climate change."--Back cover.
Surging Glacier KolkaThe Altai; Dynamics of Glaciers of Katunsky, Severo-Chuisky, and Yuzhno-Chuisky Ranges; Kuznetsk Alatau; East Sayan; Baikal Ridge; Barguzin Ridge; Kodar Ridge; GLACIER SYSTEMS RECEIVING MOISTURE FROM PACIFIC. CHUKOTKA, KORYAK, KOLYMA, CHERSKY, SUNTAR-HAYATA, KAMCHATKA; Chukotka Upland; Koryak Upland; Kolyma Upland; Chersky Mountains; Suntar-Khayata Mountains; Kamchatka; Data and Research Methodology; Contemporary Condition of Glaciers in Kamchatka and Its Variations; Sredinny Range; Kronotsky Peninsula; Volcano Group Klyuchevskaya (Fig. 2.39); Southeast Kamchatka.
THE TREND IN DYNAMICS OF MOUNTAIN GLACIERS IN RUSSIA.
Print version record.
Keywords: Alpine regions -- Environmental conditions; Mountain ecology; Hydrologic cycle; SCIENCE / Earth Sciences / Geography; SCIENCE / Earth Sciences / Geology; Hydrologic cycle; Mountain ecology; Electronic books